(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
Latin American constitutional context. Principles guiding the regulation of the religious factor and the status of women in the family sphere ABSTRACT: Bearing in mind the importance of constitutions in the field of legal systems, and being interested in knowing the legal status of women in the geographical area of Latin America, I turned to the constitutions of the countries in that area, starting from the analysis of the models of treatment of the religious fact chosen by the drafters of the constitutions and trying to locate the possible influence of these in the shaping of the rights of women considered as a fundamental part of the family.